Effect of microencapsulated/photoresistant extract of Azadirachta indica A. Juss seeds on Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctudae) and its persistence in semi-field - Bezerra, Debborah Gonçalves; Beghelli, Gabriel Modesto; Albernaz-Godinho, Karina Cordeiro; Czepak, Cecília; Conceição, Edemilson Cardoso da; Devilla, Ivano Alessandro; Paula, Joelma Abadia Marciano de (Journal of Asia-Pacific entomology, 2024)
[Display omitted] •Preparations based on Azadirachta indica seeds are biopesticides.•Microencapsulation of herbal extracts can protect the active compounds from UV rays.•Microencapsulated dry extract of A. indica controls Spodoptera frugiperda effectively.•Microencapsulated dry extract of A. indica seeds is slightly to moderately persistent. The development of bioinsecticides as an alternative to synthetic insecticides can benefit the economy of exporting and importing countries, family farming, production of high-quality commodities, food security, quality of life, and the natural environment. This study aimed to evaluate the effect of microencapsulated extracts of Azadirachta indica A. Juss on Spodoptera frugiperda J.E. Smith and their persistence in the plant under semi-field conditions. The fresh seeds of A. indica, collected in Brazil, were separated for the preparation of the microencapsulated dry extract (MDE) according to criteria registered in the patent. Lethal concentrations for S. frugiperda were determined using a dose response curve. The treatments were compared: MDE, control and positive control based on azadirachtin, evaluating mortality and growth inhibition. There was a significant difference in mortality between the treatments tested. The lethal concentrations LC50 and LC95, expressed in azadirachtin for the bioinsecticide, were 194.98 and 630.95 ppm, respectively. The growth inhibition of S. frugiperda was above 98 % in the treatments, except for the control. The MDE presented lethal times LT50 and LT90 lower than the other treatments (lethal time LT50 = 2.79 d; lethal time LT90 = 3.97 d). The MDE of A. indica seeds was effective in controlling S. frugiperda up to the fifth instar and is considered as slightly persistent to persistent depending on environmental conditions and irrigation, based on IOBC/WPRS parameters. The MDE has the potential to be a phytosanitary product approved for use in organic agriculture and with greater effectiveness in controlling S. frugiperda compared to similar pesticides. Abbreviations: BOD, Biochemical Oxygen Demand; CPA, commercial product based on azadirachtin; CLE, concentrated liquid extract; DAS, days after spraying; GI, growth inhibition; LC50, lethal concentration for 50% of the population; LC95, lethal concentration for 95% of the population; LT50, lethal time for 50% of the population; LT90, lethal time for 90% of the population; MDE, microencapsulated dry extract.